A comparative study in creative thinking and study habits among students of the Faculty of Physical Education - Dawood, Thaer; Kellan, Baydaa (Journal of Physical Education, 2010)
The students represent the essence and purpose of the educational process, content and due to the fact that academic achievement, good is not achieved acceptable manner to meet the objectives and requirements of the educational process is not exercised students good study habits because weaknesses in academic achievement is not due to the low degree of intelligence or lack of effort of the educated or non-tilt to study or engage in sporting activities but because of the move away from the optimal use of the procedures and methods used by students when dealing with the requirements of the educational situation so should contribute to the learning styles and methods and to engage in sports activities in the development of innovative thinking among the students of the Faculty of Physical Education, and the importance of research is being an attempt to identify the differences between individual students and students of the Faculty of Physical Education / University of Baghdad in the capabilities of creative thinking (fluency, flexibility and originality) and academic achievement, and depending on the different school stages.The objectives of the research are:1.Identify the degree of innovative thinking among the students of the Faculty of Physical Education / University of Baghdad.2.Recognize the significance of the differences in the capabilities of innovative thinking among students and three female students.3.Recognize the significance of the differences in the capabilities of innovative thinking among the three first-grade students and fourth.4.Identify the study habits of students of the Faculty of Physical Education / University of Baghdad.5.Recognize the significance of differences in study habits between male and female students.6.Recognize the significance of differences in study habits between students of the first row and fourth.The traditional sample of students in grades first and fourth in the Physical Education College / University of Baghdad for the academic year 2008 - 2009 m's (240) students, was the use of tools the first to measure the innovative thinking and the second to measure the study habits of university students, after processing the data statistically presented and interpreted and that was reached the following conclusions following:1.That students of the Faculty of Physical Education / University of Baghdad, have the capacity of fluency more of my ability and originality, flexibility and possessing the ability of flexibility was much higher than the capacity of originality.2.There are impacts for undergraduate study in the growth of innovative thinking, because fourth-graders have had more impact than the first-grade students.3.The students of the Faculty of Physical Education / University of Baghdad, to have all the creative thinking abilities are better than that of the students.4.That fourth-graders were practicing the habits of study better than first-grade students.5.The students of the Faculty of Physical Education / University of Baghdad, to have the practice of study habits are better than that of the students.While the recommendations were as follows:1.Tdrisie the Physical Education College / University of Baghdad, under the guidance of students towards the practice of positive study habits in the practical and theoretical lessons.2.Preparation programs for college students working on the development of innovative thinking to have.3.Provide counseling services to first-grade students work to help them to identify the values and methods of undergraduate university study and academic habits.4.The possibility of doing similar studies through the application of scales on the samples were not addressed the present study.